2017
DOI: 10.1080/10413200.2017.1306728
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Skills and “the Paras”: The Indirect Effects of Psychological Skills on Endurance

Abstract: We examined the indirect effects of basic psychological skills (PS) on military endurance through enhanced advanced PS, whilst controlling for fitness. British Army recruits (n = 159) participated in three endurance events for Parachute Regiment selection and completed an adapted Test of Performance Strategies questionnaire (Hardy etal., 2010). Following confirmatory factor analyses, the multiple mediation regression analyses using PROCESS (Hayes, 2013) suggested that goal-setting, imagery and relaxation all h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
1
20
0
2
Order By: Relevance
“…Specifically, the instrument measures the quantity of use rather than the quality 312 of use (i.e., how much one uses the skills/techniques, rather than how good or effective one is 313 at implementing them). A previously contextually modified version of the TOPS-2, which 314 was shown to demonstrate good psychometric properties with a similar sample population 315 (Arthur et al, 2017), was used to assess recruits' use of psychological skills in training (i.e., 316 pre and post-intervention) and during P-Company. In the current research we only used the 317 four basic psychological skills subscales that assess the extent to which recruits make use of 318 psychological skills.…”
Section: Test Of Performance Strategies the Test Of Performance Stramentioning
confidence: 99%
“…Specifically, the instrument measures the quantity of use rather than the quality 312 of use (i.e., how much one uses the skills/techniques, rather than how good or effective one is 313 at implementing them). A previously contextually modified version of the TOPS-2, which 314 was shown to demonstrate good psychometric properties with a similar sample population 315 (Arthur et al, 2017), was used to assess recruits' use of psychological skills in training (i.e., 316 pre and post-intervention) and during P-Company. In the current research we only used the 317 four basic psychological skills subscales that assess the extent to which recruits make use of 318 psychological skills.…”
Section: Test Of Performance Strategies the Test Of Performance Stramentioning
confidence: 99%
“…Indeed, multiple PS frameworks (e.g., Durand-Bush, Salmela, & Green-Demers, 2001;Smith, Schutz, Smoll, & Ptacek, 1995;Vealey, 1988) often fail to provide clear distinctions between mental skills (e.g., imagery, goal setting) and other cognitions and/or attributes (e.g., confidence, motivation; cf. Arthur, Fitzwater, Roberts, Hardy, & Arthur, 2017). To advance clarity, we…”
Section: Conceptualization Of Psmentioning
confidence: 99%
“…To ensure conceptual clarity in the current research program we align with Hardy and colleagues' (Hardy, Roberts, Thomas, & Murphy, 2010;Thomas, Murphy, & Hardy, 1999) proposal that there are basic cognitive-affective PS (i.e., goal setting, imagery, relaxation and self-talk), and more advanced PS which are indictors of ability (e.g., emotional control, automaticity, attentional control). Performers who practice using basic PS will eventually improve their ability with the more advanced PS, which will ultimately influence performance (see Arthur et al, 2017 for evidence of this effect). To provide a foundation for an appropriate coaching PS measure we focused on the coaching of basic PS defined as cognitive-affective skills (i.e., imagery, goal setting, self-talk and relaxation) which can be learnt, practiced and carried out alongside, or in addition to physical sports performance.…”
Section: Conceptualization Of Psmentioning
confidence: 99%
“…The role of psychological characteristics is relevant not only due to its direct impact on athlete’s performance (e.g., coping with or choking under stress), but also as a mediator between the athlete’s physical, technical, and tactical skills and his/her performance in competition, whether positively or negatively (Mahamud et al, 2005; Anderson et al, 2014; Arthur et al, 2017). In this vein, some seminal studies found that the physiological variables accounted for between 45 and 48% of the sport performance, but when psychological variables were added, the percentage of variance explained rose to about 79% and 85% in sports such as wrestling (Nagle et al, 1975; Silva et al, 1981; James et al, 2016).…”
Section: Introductionmentioning
confidence: 99%